2007
DOI: 10.1073/pnas.0700416104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms controlling the acquisition of a cardiac phenotype by liver stem cells

Abstract: The mechanisms underlying stem cell acquisition of a cardiac phenotype are unresolved. We studied early events during the acquisition of a cardiac phenotype by a cloned adult liver stem cell line (WB F344) in a cardiac microenvironment. WB F344 cells express a priori the transcription factors GATA4 and SRF, connexin 43 in the cell membrane, and myoinositol 1,4,5-triphosphate receptor in the perinuclear region. calcium signal transduction ͉ cardiomyogenesis ͉ gap junctions E xtracardiac stem cell use in early p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 36 publications
(38 reference statements)
8
33
0
Order By: Relevance
“…In this regard, myocd can initiate the expression of cardiac muscle-specified genes in cultured fibroblasts, but only in the presence of the co-expressed small ubiquitinlike modifier, SUMO-1 . Undifferentiated liverderived stem cells acquire a cardiomyocyte phenotype when cocultivated in vitro with neonatal cardiomyocytes which, in turn, results in the de novo activation of cardiac transcriptional factors including myocd (Muller-Borer et al, 2007). These and other data (Oh et al, 2004;Callis et al, 2005;Creemers et al, 2006a) strongly suggest that additional factors are required to promote myocardin's role in cardiogenic gene expression.…”
Section: Introductionmentioning
confidence: 75%
“…In this regard, myocd can initiate the expression of cardiac muscle-specified genes in cultured fibroblasts, but only in the presence of the co-expressed small ubiquitinlike modifier, SUMO-1 . Undifferentiated liverderived stem cells acquire a cardiomyocyte phenotype when cocultivated in vitro with neonatal cardiomyocytes which, in turn, results in the de novo activation of cardiac transcriptional factors including myocd (Muller-Borer et al, 2007). These and other data (Oh et al, 2004;Callis et al, 2005;Creemers et al, 2006a) strongly suggest that additional factors are required to promote myocardin's role in cardiogenic gene expression.…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, these fetal AM hMSCs were able to differentiate, in coculture with nrCMCs, into functional CMCs, while adult AT hMSCs were not [19]. Other investigators using cocultures with CMCs to induce cardiomyogenic differentiation in stem cells have also proposed that intercellular communication through gap junctions might be essential in this differentiation process [33,34]. However, the role of gap junctional communication in the transfer of cardiomyogenic signals from CMCs to other cell types has not yet been investigated.…”
Section: Role Of Gap Junctional Communication In Cardiomyogenic Diffementioning
confidence: 99%
“…In line with these findings are the observations by Muller-Borer et al who found that in coculture with nrCMCs, rat liver stem cells obtain CMC-like properties and display [Ca 2þ ] oscillations synchronous with those of adjoining CMCs. The [Ca 2þ ] oscillations in the liver stem cells were dependent on gap junctional communication with neighboring CMCs and their inhibition led to a decrease in the expression of CMC-specific genes by the liver stem cells [34]. The recent observation that hyperpolarization is sufficient to induce cardiomyogenic differentiation of human CMC progenitor cells underlines the importance of gap junctional coupling in this process [12].…”
Section: Role Of Gap Junctional Communication In Cardiomyogenic Diffementioning
confidence: 99%
“…We chose this model to maximize our ability to differentiate between host and transplanted cells using species specific markers.While we used GFP to label cells, other methods such as antibodies to human mitochondria could have been used as well [35]. Concern may be raised about the xenogenic immune response that could be elicited from these injections.…”
Section: Discussionmentioning
confidence: 99%